Spatial distribution model of anoa, Bubalus spp., in Tanjung Peropa Wildlife Reserve - Ola Aso; Abdul Mustari; Lilik Prasetyo (Biodiversity Data Journal, 2025)
Anoa (Bubalus spp.) are an endemic species that inhabits the forests of Sulawesi, but are threatened with extinction due to hunting and habitat destruction. Despite these pressures, they temporally adapt to fragmented lowland forests near rivers with food availability. In the Tanjung Peropa Wildlife Reserve, an isolated habitat patch, we used MaxEnt modelling to assess environmental factors influencing their distribution in support of a comprehensive species conservation programme. We used 233 anoa presence data points from footprints, faeces, food remnants, horn rubbing marks, wallowing areas and shelter locations during field surveys and 13 environmental variables. The MaxEnt model showed excellent performance (AUC 0.923), fruit-feeding trees presence contributing most (41.1%), followed by distance to the road, perimeter metrics, distance to the river, elevation and large patch index metrics. The results show that 1,239.8 ha (3.2%) of the study area is suitable for anoa as primary habitat, 3,045.1 ha (7.8%) is moderately suitable as secondary habitat and 6,609.8 ha (17.0%) is unsuitable out of the total 38,937 ha study area, while the remaining 28,042.3 (72.0%) is undefined due to lack of occurrence data. The anoa distribution map shows that the edge of the area can still provide for the ecological needs of the anoa, highlighting the need for patrols, community education and further surveys of identified and undefined areas.